Register dalam Komunikasi Waria di Kembang Kuning Surabaya - Damayanti, Rini (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2018)
The register is a variety of languages that are used for a specific purpose, as opposed to social or regional dialects (which vary because the speakers) these registers can be restricted to a narrower one with reference to the subject matter. The purpose of this study was to obtain descriptions of registers, transgender languages in daily communication in the Kembang Kuning area of Surabaya. The method used in this study is a qualitative descriptive method. The object in this study was shemale in the Kembang Kuning area of Surabaya. The technique used in this research is recording techniques, transcripts / notes that are used to record the results of conversations. Based on the presentation of the results of the study and discussion, it was concluded that there were several types of sentences used by the Waria community in the Surabaya Kembang Kuning area which included news sentences (declarative), interrogative sentences, and imperative sentences.Keywords: register; shemale